2009
DOI: 10.3945/ajcn.2008.27023
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic activity of the enteric microbiota influences the fatty acid composition of murine and porcine liver and adipose tissues

Abstract: These results are consistent with the concept that the metabolome is a composite of host and microbe metabolic activity and that the influence of the microbiota on host fatty acid composition can be manipulated by oral administration of CLA-producing microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 171 publications
(130 citation statements)
references
References 53 publications
5
124
0
1
Order By: Relevance
“…There were no significant differences in the mRNA levels of cytokines after B. breve administration in this study. O'Mahony et al (24) reported a model of cytokine production under stimulation with anti-CD3 and anti-CD28 antibodies using splenocytes. Because our study simply examined the mRNA levels of cytokines and other signaling molecules without any stimulation, we cannot directly compare our results to theirs.…”
Section: Articlesmentioning
confidence: 99%
“…There were no significant differences in the mRNA levels of cytokines after B. breve administration in this study. O'Mahony et al (24) reported a model of cytokine production under stimulation with anti-CD3 and anti-CD28 antibodies using splenocytes. Because our study simply examined the mRNA levels of cytokines and other signaling molecules without any stimulation, we cannot directly compare our results to theirs.…”
Section: Articlesmentioning
confidence: 99%
“…Host-microbe interactions can together co-metabolise dietary components to produce a large array of molecules with beneficial impacts on health. Commensal bacteria have been shown to synthesise essential vitamins such as vitamin K 2 and B vitamins (79) , can alter n-3 PUFA metabolism to generate increased levels of long-chain PUFA metabolites such as EPA and DHA (80,81) , can produce conjugated fatty acid derivatives of PUFA such as conjugated linoleic acid (CLA) and conjugated α-linolenic acid (82,83) and can increase production of SCFA (81) . The beneficial impacts of some of these bioactive compounds on host health are reviewed later and summarised in Table 1.…”
Section: Microbial Metabolism Of Choline and Cvdmentioning
confidence: 99%
“…However, only a few studies have established CLA production in vivo following ingestion of a CLA-producing bacterium. For example, the in vivo production of t10, c12 CLA by Lactobacillus rhamnosus PL60 and Lactobacillus plantarum PL62 was reported (Lee et al, 2006a(Lee et al, , 2007, and we recently demonstrated that feeding different animal species a c9, t11 CLA-producing Bifidobacterium strain of human origin (Bifidobacterium breve NCIMB 702258), in combination with dietary linoleic acid, resulted in modulation of the fatty acid composition of the host, including significantly elevated concentrations of c9, t11 CLA in the liver (Wall et al, 2009). …”
Section: Introductionmentioning
confidence: 99%